Coping with Globalization : Cross-National Patterns in Domestic Governance and Policy Performance. - Chan, Steve (Taylor and Francis, 2013)
This volume probes the interactions between domestic and international political economies, and inquires about their effects in different regional and national contexts. The contributors seek to identify persistent patterns as well as changing trends in regard to these important questions of theory and policy by applying systematic cross-national analyses.